Video In Situ Snowfall Sensor (VISSS) data for Ny-Ålesund on 2024-03-05 - Maximilian Maahn; Nina Maherndl; Nils Pfeifer (PANGAEA, 2025)
The VISSS is a camera system recording precipitating snowfall from two perspectives. Here, movies and images of falling precipitation particles are provided for one day at station Ny-Ålesund. For further details on the VISSS see Maahn et al. (2024).
In: Maahn, M et al. (2025): Video In Situ Snowfall Sensor (VISSS) data for Ny-Ålesund (January 2024 - December 2024) [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.981436